Niveles de actividad física y control del sedentarismo en niños - Porras Jimenez, Jimmy Javier (2024)
The main objective of the present research study entitle “Niveles de actividad física y control del sedentarismo en niños”, aims to determine the levels of physical activity and sedentary lifestyle control in children in the sixth year of the sixth parallel "C" of basic education of the Leopoldo Freire Educational Unit of the canton Chambo, through the application of pre-sport activity focused on active soccer, responds to a quantitative research approach, seeks to describe, explain, verify and predict phenomena (causality), generate and test theories. Therefore, data are collected with standardized and validated instruments such as the Physical Activity Survey for Children and Adolescents (PAQ-A). The research is classified as quasi-experimental because it involves the manipulation of an independent variable, in this case, a specific intervention, and the observation of its effects on a dependent variable, without random assignment of subjects to the control and experimental groups. This design allows comparing changes before and after the intervention within the same group. The type of research has a cross-sectional quantitative approach, since the results obtained are numerical and were obtained from the application of quantitative instruments in a specific period of time. The results suggest that the intervention had a very significant impact when applying the "Physical Activity Questionnaire for Children and Adolescents" (PAQ-A), also the normality analyses and paired tests support these findings generating a positive impact, highlighting the importance of considering individual variability and the adequacy of the statistical methods used.